Tingkat kepuasan pelayanan pasien BPJS kesehatan terhadap pelayanan obat di apotek X Kota Sibolga - Salmah Handayani Lubis; Fenny Hasanah; Eva Sartika Dasopang; Lathifur Rasyidah Tanjung (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Health-related issues are one of the most pressing needs of society. Indonesia has government-run health insurance that is directly under its control. When patients obtain services that are considered appropriate or above expectations, patient satisfaction is achieved. This research uses a survey research approach and is descriptive. Surveys distributed to respondents were used to collect data. Eighty respondents who met the inclusion requirements were sampled. The data used is primary data, information obtained directly from respondents, with data collection methods such as providing questionnaires, which are filled in by the respondents themselves and sent back to the researcher. The findings of the study, which were based on SPSS patient characteristics analysis, showed that females accounted for the most significant percentage of respondents (43), followed by the 46-55 years age group (32.5%) and housewives (27.5%), (n=26; 32.5%) had the highest hypertension diagnosis on SPSS analysis, while (n=18; 69%) had the highest drug name of amlodipine. The results, according to the Servqual model, showed that the guarantee dimension had the largest average of 98%(Assurance), while the responsiveness dimension had the lowest average of 92% (waiting time).